2010
DOI: 10.1523/jneurosci.5560-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Consumption of a High-Fat Diet during Pregnancy Causes Perturbations in the Serotonergic System and Increased Anxiety-Like Behavior in Nonhuman Primate Offspring

Abstract: Childhood obesity is associated with increased risk of behavioral/psychological disorders including depression, anxiety, poor learning, and attention deficient disorder. As the majority of women of child-bearing age are overweight or obese and consume a diet high in dietary fat, it is critical to examine the consequences of maternal overnutrition on the development of brain circuitry that regulates offspring behavior. Using a nonhuman primate model of diet-induced obesity, we found that maternal high-fat diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
288
2
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(310 citation statements)
references
References 34 publications
(38 reference statements)
14
288
2
6
Order By: Relevance
“…In animals, maternal consumption of a high-fat diet has been linked to a range of negative CNS outcomes, including increased anxiety-like behaviors, 31,32 decreased hippocampal dendritic arborization, 33 increased hypothalamic neurogenesis of orexigenic neurons (which can drive overeating and increase the obesity risk) 34 and alterations in the expression of serotonergic genes, dopaminergic genes, inflammation-related genes and neuropeptides related to food intake/metabolism. 31,32,34,35 Not all areas of the brain appear to be similarly sensitive to the effects of maternal consumption of a high-fat diet, as arcuate to paraventricular projections are not affected by maternal diet, 36 yet these projections are affected by maternal insulin status, 37 highlighting the complexity of the interactions between maternal environment (diet, obesity, diabetes) and the offspring outcome.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In animals, maternal consumption of a high-fat diet has been linked to a range of negative CNS outcomes, including increased anxiety-like behaviors, 31,32 decreased hippocampal dendritic arborization, 33 increased hypothalamic neurogenesis of orexigenic neurons (which can drive overeating and increase the obesity risk) 34 and alterations in the expression of serotonergic genes, dopaminergic genes, inflammation-related genes and neuropeptides related to food intake/metabolism. 31,32,34,35 Not all areas of the brain appear to be similarly sensitive to the effects of maternal consumption of a high-fat diet, as arcuate to paraventricular projections are not affected by maternal diet, 36 yet these projections are affected by maternal insulin status, 37 highlighting the complexity of the interactions between maternal environment (diet, obesity, diabetes) and the offspring outcome.…”
Section: Animal Modelsmentioning
confidence: 99%
“…31,32,34,35 Not all areas of the brain appear to be similarly sensitive to the effects of maternal consumption of a high-fat diet, as arcuate to paraventricular projections are not affected by maternal diet, 36 yet these projections are affected by maternal insulin status, 37 highlighting the complexity of the interactions between maternal environment (diet, obesity, diabetes) and the offspring outcome.…”
Section: Animal Modelsmentioning
confidence: 99%
“…As both maternal nutrition and obesity influence the development of mammals during the intrauterine or breastfeeding phases (Sullivan et al 2010), scientific interest was directed to elucidate the influence of maternal obesity (MO) on the physiology of organs and health during childhood and adult life. Epidemiological and animal model studies indicated that MO at conception alters gestational metabolic adjustments and affects placental, embryonic, and fetal growth and also postnatal development (Catalano & Ehrenberg 2006, Catalano et al 2009, Symonds & Budge 2009, Sullivan et al 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Several lines of evidence show that acute or chronic stimuli during gestation can induce a permanent response in fetus and impair the physiology of several organic systems and this phenomena was designed fetal programming (Dabelea et al 2000, Boney et al 2005, Sewell et al 2006, Catalano et al 2009, Symonds & Budge 2009). The effects of MO on fetal programming of energy balance and adiposity (Sullivan et al 2010) and cardiovascular and renal systems (Nistala et al 2011) had been described. However, the knowledge about consequences of MO on fetal programming and histophysiology of the genital system is incipient, and there is no information about the potential interference of MO on testis development at neonatal life.…”
Section: Introductionmentioning
confidence: 99%
“…All animal protocol work is approved by and in accordance with the relevant guidelines and regulations as stated by the institutional animal care and use committees (IACUC) at both Baylor College of Medicine (protocol number AN-4752) and the Oregon National Primate Research Center (ONPRC). Experimental design: The use of M. fuscata by our consortium of investigators has been previously described [24][25][26][27][28][29][30][31][32][33] . In brief, animals are socially housed (4-9 females and 1-2 males per group) within indoor/outdoor enclosures at the Oregon National Primate Research Center (ONPRC).…”
Section: Methodsmentioning
confidence: 99%